May We Strengthen the Human Natural Defenses with Bacterial Lysates? - Villa, Elisa (World Allergy Organization, 2010)
During the last twenty years bacterial lysates have gained a new interest and their use has obtained a progressively larger consensus in the medical practice. They are commonly used as immunomodulators, in order to up-regulate immune responses against infectious damages. As a matter of fact, the role of these lysate seems relevant in upper and lower respiratory tract infections prevention, frequently observed both in paediatric and elder ages, and which represent a relevant problem also in terms of socio-economical implications. The effects of bacterial lysates as immunostimulatory agents have become the central point of many studies. The aim of those in vivo and in vitro studies was to understand and evaluate the capacity of this kind of treatments to create a better answer of the immune system against microbial infections, eventually leading to a reduction in their number. All the in vivo and in vitro findings analyzed support the evidence that bacterial lysates are powerful inducers of a specific immune response against bacterial infections. Both in paediatric and adult clinical trials, a positive trend has been found in terms of overall reduction of infection rates and duration, beneficial effect on symptoms, reduction in antibiotics use and possibility to improve the patient's quality of life in several diseases. Further well-designed trials in terms of blinding and randomization procedures and including a higher number of patients, selected according to the disease and its severity, are needed.